PENGARUH INTERAKSI ANTARA TOTAL QUALITY MANAGEMENT DENGAN SISTEM PENGHARGAAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL Studi Empiris pada SMK Di Kabupaten Karanganyar - Mardiyati, Endang Mardiyati (PARADIGMA, 2015)
This emperical research conducted 2014, is intended to test the hyphothesisabout the influences variables of TQM, interaction between TQM with rewardsystem, and interaction between TQM with organizational commitment tomanagerial performance at the level of SMK in Karanganyar. The research design is survey and quantitative approach. Respondents were teachers and employees in the SMK of public and private school in Karanganyar, who held managerial positions amounted to 142 pearsons from 33 schools. It usesthe regression with the absolute residual test method to test hypothesis.The results of this research showed that the proposed third hypothesis can beaccepted, meaning that TQM (X1), interaction between TQM with reward system (X2) and interaction between TQM with organizational commitment (X3) have positive and significant effect on managerial performance. Keywords : TQM, reward